Answer:
For the given functions f(x) and g(x) [tex](f-g)(x) = -2x^{2} - 8x +12[/tex]
Step-by-step explanation:
Here, the given function are:
[tex]f(x) = 3x^{2} - 2x+ 4\\g(x) = 5x^{2} + 6x -8[/tex]
Now, simplifying for (f-g)(x) = f(x) - g(x):
[tex]f(x) - g(x) = (3x^{2} - 2x+ 4) - (5x^{2} + 6x -8)[/tex]
[tex]= 3x^{2} - 2x+ 4- 5x^{2} - 6x +8[/tex]
Doing operation on LIKE TERMS, we get
f(x) - g(x) = [tex]( 3x^{2}- 5x^{2}) + (-2x - 6x) +( 4 +8) = -2x^{2} - 8x + 12[/tex]
Hence, for the given functions f(x) and g(x) [tex](f-g)(x) = -2x^{2} - 8x +12[/tex]